A case study of circular economy from waste - Do Van Manh,; Nguyen Tuan Minh,; Le Xuan Thanh Thao,; Huynh Duc Long,; Luong Huu Thanh,; Vu Dinh Ngo,; Dang Thi Thom, (Vietnam Journal of Science and Technology, 2023)
This case study focused on zero emission via waste sludge treatment process from a brewery wastewater treatment plant. A perspective solution was based on three main processes by sludge digestion (40 m3/day), biogas recovery and purification for generation (20 kWh) and organic fertilizer production for green agriculture. The system is designed to integrated processes and operated autocompletively, except for the fertilization of crops. This work results showed that organic content decreased 55 - 70% after 20 days of sludge retention time (SRT) with 55 - 65% methane (CH4) yield. The contaminants in biogas was purified by high gravity rotating packed bed (HGRPB) device using aqueous solution (NaOH 0.01 M) and removal efficiency of CH4 concentration is 87%, this CH4 content met a demand of the standard for generator engines or boiler combustion. The digested sludge was combined with other by-products to produce organic fertilizer for green agricultural development, the quality of organic fertilizer was examined and met the regulations of Decree No. 84/2019/ND-CP of the Government: Regulations on fertilizer management. The achievements of this case study respond the harmonious combination among waste treatment, energy recovery and organic fertilizer production to contribute to the direction of the circular economy aspect and sustainable development.